Peningkatan Kemampuan Mengenal Huruf Pada Anak Usia 5-6 Tahun Melalui Metode Bermain Dengan Media Kotak Pintar - Sheila Septiana Rahayuningsih; Tritjahjo Danny Soesilo; Mozes Kurniawan (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
This study aims to improve the ability to recognize letters through the method of playing with the smart box media for children aged 5-6 years in Sion Blora Kindergarten. The activities to identify letters using the smart box media is able to motivate children's interest to learn. This classroom action research was conducted in two cycles with three meetings in each cycle. The subjects of the study were 14 children aged 5-6 years. The data collection was done with interviews, observation, and documentation. The research instrument referred to Permendikbud (Regulation by the Minister of Education and Culture) Number 146 Year 2014. The observation was done with the assessment sheets, documentation, and interviews with the classroom teachers to determine the conditions and problems of children in the classroom, analyzed with a descriptive quantitative technique. The success indicator of this research is 90% for the average value. The results showed an increase in the average score from the pre-cycle of 14,29% to 60,71% in cycle I; up to 92.86% in cycle II. Thus, it can be said that the percentage of success reached ≥ 90%.